2014
DOI: 10.1093/imaiai/iau006
|View full text |Cite
|
Sign up to set email alerts
|

1-Bit matrix completion

Abstract: In this paper we develop a theory of matrix completion for the extreme case of noisy 1-bit observations. Instead of observing a subset of the real-valued entries of a matrix M , we obtain a small number of binary (1-bit) measurements generated according to a probability distribution determined by the realvalued entries of M . The central question we ask is whether or not it is possible to obtain an accurate estimate of M from this data. In general this would seem impossible, but we show that the maximum likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
305
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(316 citation statements)
references
References 56 publications
(99 reference statements)
11
305
0
Order By: Relevance
“…There, it was shown that amplitude information about the transmitted signal can be recovered even in the presence of a single-bit quantizer, provided that the number of receive antennas is sufficiently large and the signalto-noise ratio (SNR) is not too high. The observation that noise can help recovering magnitude information under 1-bit quantization has also been made in the compressive-sensing literature [9], [10].…”
Section: B Relevant Prior Artmentioning
confidence: 81%
See 1 more Smart Citation
“…There, it was shown that amplitude information about the transmitted signal can be recovered even in the presence of a single-bit quantizer, provided that the number of receive antennas is sufficiently large and the signalto-noise ratio (SNR) is not too high. The observation that noise can help recovering magnitude information under 1-bit quantization has also been made in the compressive-sensing literature [9], [10].…”
Section: B Relevant Prior Artmentioning
confidence: 81%
“…In the above problem,ŷ w , w ∈ {Ω pilot ∪ Ω pilot }, are the frequency-domain entries of the matrices H w , w ∈ {Ω pilot ∪ Ω pilot } that correspond to the uth user and the bth BS antenna, which are estimated using the orthonormal pilot matrices T w (see Section IV-B). Although (MQ-CHE) has a closedform solution, 9 we will use a first-order method to reduce both computational complexity and memory requirements (see Section V). In practice, one can also obtain approximate solutions to (MQ-CHE) using more efficient methods (see e.g., [50]).…”
Section: Mismatched Quantization Models 1) First Mismatched Quantimentioning
confidence: 99%
“…Furthermore, the techniques outlined in the proof section our general and can be applied to a variety of sampling operators for matrix completion. For example, a simple modification of our proof yields a different class of results for the "one-bit" matrix completion problem [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we might suppose that the entries of A are generated as noisy, 1-bit observations from an underlying low rank matrix XY . Surprisingly, it is possible to accurately estimate the underlying matrix with only a few observations |Ω| from the matrix by solving problem (18) (under a few mild technical conditions) with an appropriate loss function [DPBW12].…”
Section: Examplesmentioning
confidence: 99%